Patterning by Selective Etching of Poly-Silicon Using a High Etch Rate Single Sided Gaseous Process - Laurent Clochard; David Young; Mingzhe Yu; Ruy Sebastian Bonilla (SiliconPV Conference Proceedings)
This paper presents etching process developments using a single-side gaseous etch process based on the thermal reaction of poly-Silicon and the etching gas (molecular fluorine), that results in a high etching selectivity between layers, and a high etching rate. This work was carried out in the context of the development of solar cell architectures beyond PERC and TOPCon, where more sophisticated etching steps are required in order to accurately pattern poly-silicon layers across the wafer surface.